Immunomodulatory effects of β-defensin 2 on tumor associated macrophages induced antitumor function in breast cancer - Sonam Agarwal; Anita Chauhan; Pramod Kumar Gautam (Advances in Cancer Biology - Metastasis, 2023)
Background: Tumor-associated macrophages (TAMs) express cytokines and chemokines that can suppress antitumor immunity and promote tumor progression. The immunomodulatory and antitumor function of β-defensin 2 is still unclear, despite the evidence of infection response. We previously reported that β-defensin 2 modulates immunomodulatory and their antitumor function of macrophages in breast cancer. We investigate the association between β-defensin 2 and TAMs and determined the role in tumor-promoting attributes of TAMs reversal of phenotype in tumor regression. Methods: Swiss albino mice and C127i breast cancer cell line was used in this study. C127i conditioned media was prepared and generated macrophage-derived TAMs to study antitumor function. Flow cytometry was performed for phenotype identification of macrophages and TAMs. MTT assay was performed to estimate cytotoxicity and dose optimization of β-defensin 2. Oxidative stress was analyzed by H2O2 and NO estimation, and qPCR was performed for iNOS, cytokines and chemokines expression. Results: PEC harvested macrophages were characterized by flow-cytometry using F4/80, CD11c antibodies with 98% pure population of macrophages and cultured in C127i conditioned media for 7 days. TAMs markers were estimated, and it was found that 98% expression of F4/80, CD-206, and CD-115 expression compared to macrophages. Purified 100 ng/ml of β-defensin 2 was used to stimulate the TAMs population was viable, which was confirmed by cell viability assay. ROS levels decreased in TAMs treated with β-defensin 2 compared to control group. Interleukins (ILs)-6, 10, and 3, tumor necrosis factor (TNF)-α, and transforming growth factor (TGF)-β and chemokine ligand (CXCL)-1, 5 and 15, chemokine ligand (CCL)-24 and 5 decreased drastically compared to control. Conclusion: This is the first report of β-defensin 2 on TAMs to elucidate the immunomodulatory and anti-tumor function. It was found that the cytokines, chemokines, and reactive oxygen species (ROS) expression pliably changed which facilitates tumor regression. β-defensin 2 must be targets as adjuvant for future cancer immunotherapeutic agent.